2018
DOI: 10.29252/pcnm.8.2.26
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thermal Care Workshop on EMS Staff Readiness in managing Accidental Hypothermia in Trauma Patients

Abstract: Background: Hypothermia is a common complication in trauma patients. Studies show that the management of hypothermia in trauma patients in the pre-hospital phase may be underestimated. Objectives: The purpose of this study was to evaluate the effect of thermal care workshop on the staff readiness to manage hypothermia in trauma patients. Methods: This quasi-experimental study utilized convenience sampling after obtaining the approval of the Research Ethics Committee and involved 60 qualified EMS staff who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
2
3
0
Order By: Relevance
“…Nurses’ knowledge and practice were higher among nurses who received training related to hypothermia prevention compared with those who did not. This finding is supported by other studies in America, 38 Brazil, 41 Iran 26 and Turkey. 4 This can be explained by the fact that training plays an important role in improving the quality of patient care.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Nurses’ knowledge and practice were higher among nurses who received training related to hypothermia prevention compared with those who did not. This finding is supported by other studies in America, 38 Brazil, 41 Iran 26 and Turkey. 4 This can be explained by the fact that training plays an important role in improving the quality of patient care.…”
Section: Discussionsupporting
confidence: 87%
“…This study also dictates that nurses who had BSc and master’s degrees were more likely to have good knowledge of hypothermia prevention compared with those who only had a diploma. This finding is supported by studies conducted in Iran 26 and Brazil. 14 This implies that educational interventions are fundamental for nurses to improve their scientific knowledge, which, in turn, increase the quality of patient care.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Numerous sources, including research studies, case studies, and anecdotal information, are used to support hypothermia studies. The causes of hypothermia in the prehospital stage have not been thoroughly studied, despite the fact that many processes and several states of hypothermia are widely known and documented in the pertinent literature [11]. In these situations, it has been demonstrated that early diagnosis and treatment of hypothermia lower the severity of the injury [12,13].…”
Section: Introductionmentioning
confidence: 99%